Increased Serum Neutrophil Lymphocyte Ratio Raises the Risk for Peripheral Diabetic Neuropathy in Type 2 Diabetes Mellitus Patients - Pramaswari, Anak Agung Ayu Agung; Adnyana, I Made Oka; Widyadharma, I Putu Eka; Suastika, Ketut (Siriraj Medical Journal, 2023)
Objective: Peripheral diabetic neuropathy (PDN) is among the most prevalent diabetes mellitus (DM) sequelae. PDN is a severe health issue that represents a huge social and economic burden worldwide, is associated with long-term morbidity, and diminishes the quality of life of those affected. The neutrophil-lymphocyte ratio (NLR) is a mixture of the two primary components of chronic inflammatory diseases (high neutrophils and low lymphocytes) that contribute to the production of PDN. This study aimed to demonstrate high serum NRL levels enhance the risk of PDN in type 2 DM patients. Materials and Methods: This study employed a case-control design, collecting data from the registers and outpatient medical records of Prof. Dr. IGNG Ngoerah General Hospital type 2 DM patients who satisfied the inclusion and exclusion criteria between January 2018 and December 2019. Based on clinical neuropathy and abnormal electrodiagnostic testing, the PDN diagnosis was established. Serum NLR was collected from laboratory tests recorded by a computer. Results: The Receiver Operating Characteristic (ROC) curve approach determined the NLR cut-off value of 2.18. High NLR substantially increased the incidence of PDN (OR 10.36; 95% CI 3.69-29.07; p<0.001). Other characteristics evaluated, including duration of diabetes, usage of anti-diabetic medications, uncontrolled diabetes, obesity, hypertension, and dyslipidemia, were not significantly associated with the incidence of PDN. High serum NLR was an independent risk factor for PDN in type 2 DM patients (adjusted OR=10.36; 95% CI: 3.57-29.07; p<0.001). Conclusion: Based on the findings of this investigation, it was determined that elevated serum NLR increases the risk of PDN events in patients with type 2 DM.